INCREASING LEARNING ACTIVITIES USING COURSE REVIEW HOORAY LEARNING MODELS FOR STUDENTS OF GRADE VII - Nuha Fatin Ranjani; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This research's background problem is that the lack of students' activities in learning activities because of the learning model is not innovative. This research aims to increase students' learning activities using cooperative learning model type Course Review Hooray (CRH) on the subject of plane figures: quadrilaterals on students class VII A of Muhammadiyah Junior High School (SMP Muhammadiyah) 5 Yogyakarta the academic year 2016/2017.  These research subjects are students of class VII A of SMP Muhammadiyah 5 Yogyakarta in 2016/2017. This research's object is the mathematics learning process using cooperative learning model type CRH. The subject of plane figures: quadrilaterals on students class VII A of SMP Muhammadiyah 5 Yogyakarta. The techniques of data collection are observation and interview. The data are analyzed by qualitative descriptive analysis. This research is included in class action research consists of two cycles.  The result of this research showed that cooperative learning model type CRH could increase students' learning activities in the mathematics of class VII A in SMP Muhammadiyah 5 Yogyakarta academic year 2016/2017. It can be seen from the result of the observation sheet about students' learning activities in each cycle, which is the percentage of students’ learning activities in mathematics in cycle I is 45,63% with the criteria of enough and in cycle II was increased to 69,22% with the criteria of good. Moreover, each cycle's test result also increased, which can be seen from the test result in cycle I, which has 79,36, and in cycle II the mean was increased to 88,93.